Rebel Rivalry and the Strategic Nature of Rebel Group Ideology and Demands. (April 2021) - Tokdemir, Efe; Sedashov, Evgeny; Ogutcu-Fu, Sema Hande; Leon, Carlos E. Moreno; Berkowitz, Jeremy; Akcinaroglu, Seden
How does the presence of multiple combatants affect rebel groups' ideological and demand positioning? Although violent forms of inter-group conflict have been widely studied in the civil war literature, rebel groups' strategic use of ideology and demands has received scarce scholarly attention. We argue that the pressure of competition forces rebel groups to differentiate themselves ideologically and demand-wise from their rivals to maximize their chances of survival and success. Rebel groups strive to set themselves apart by offering unique products to their supporters and recruits. Thus, we contend that rebel groups are more likely to modify their ideologies and demands from the government in the face of competition from rival groups. We test this theory using novel data collected from rebel group manifestos and public statements. Our findings suggest that groups are more likely to shift their ideology and modify their demands as the number of rival groups increases.